Perilaku Komunikasi Antarbudaya Pasutri Kawin Campur (Perspektif Drama Turgi) - Adi, Dodot Sapto (Universitas Merdeka Malang, 2017)
Abstract Research conducted in the city of Malang, East Java in 2017, has been able to describe the behavior, and also reveal the strategy of constructing the behavior of intercultural communication in order to maintain household harmony. Similarly, regarding personal communication model, by emphasizing the factor of openness to be the main in building the values that are favored or referenced, and with that foundation also other factors in personal relationships can easily follow. The method of qualitative naturalistic analysis is interactive, becoming the basic reference for obtaining relevant data. While the use of phenomenology approach, it is useful to explore the personal experience of informants in married life, so it is easy to formulate together with informants about normative concepts that are commonly applied in pragmatic problem solving. The results of this study can find the importance of improving the behavior of intercultural communication between married couples, in order to achieve a harmony relationship through the process of understanding to position his partner and his nearest social environment. The basic principles of family communication are important in addressing common problems, and intimate communication should always be created at every opportunity. Both of these factors can run effectively, if each marriage marriage partner provides an opportunity for her partner to present her role. Keywords: married couples, intercultural communication behavior, family turgi dramaÂ DOI :Â https://doi.org/10.26905/nomosleca.v3i2.2032